GAMIFICATION FOR CLASSROOM INTERACTION - Kalayo Hasibuan; Natasya Jihan Fadila; Dinda Azizah; Iqbal Syahputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Gamification has become one of the innovative approaches in education to improve classroom interaction and student engagement. This study discusses the implementation of gamification in classroom learning activities and its impact on students’ motivation, participation, and collaboration. Gamification refers to the application of game elements such as points, badges, rewards, leaderboards, and challenges in non-game contexts, especially in education. The method used in this paper is descriptive qualitative through literature review and observation of classroom learning activities. The findings indicate that gamification can create a more interactive and enjoyable learning environment. Students become more active in discussions, more enthusiastic in completing assignments, and more cooperative in group activities. In addition, gamification also helps teachers manage classroom interaction effectively by increasing students’ attention and reducing boredom during learning sessions. However, challenges such as limited technological facilities and teachers’ lack of understanding of gamification strategies may hinder its implementation. Therefore, teachers need proper preparation and creativity in integrating gamification into classroom learning. Overall, gamification provides positive contributions to improving classroom interaction and learning experiences.